Analisis Usahatani Beberapa Varietas Unggul Padi Sawah - Fachrizal, Riza; Monika, Nova Suryawati (AGRICOLA, 2021)
This study aims to analyze the differences in rice farming production of Inpari 32, Ir 64 and Cigelis varieties in the study area, to analyze the differences in rice farming acceptance of Inpari 32, Ir 64 and Cigelis varieties in the study area, to analyze the differences in income of Inpari 32 rice field rice farming, Ir 64 and Cigelis in the study area, analyzed whether the rice cultivation of Inpari 32, Ir 64 and Cigelis varieties was feasible from the ratio of revenue and cost (R / C) in the study area. This research was conducted in Tanah Miring District, Merauke Regency. The location selection was done purposively. The population was 4,770 farmers and the sampling was done by using purposive method, 5% of the population was taken, in order to obtain a sample of 128 farmers. The analysis technique used in this research is to use cost, revenue, income, and feasibility analysis. The results show that there are differences in production, acceptance and income of Inpari 32, Ir 64 and Cigelis rice fields with an average land area of ​​1.5 ha. With the R / C of the Inpari 32 variety of 3.05 BEP, the production was 995 kg and the BEP was 2.463 / kg. The R / C of the Ir 64 variety was 2.59 with a BEP of production of 1.055 kg and a BEP of 2,930 / kg and the R / C of the Cigelis variety of 2.50 with a production BEP of 1,036 kg and a BEP of 3,312 / kg.